The Trade and Climate Change Nexus : The Urgency and Opportunities for Developing Countries - Brenton, Paul; Chemutai, Vicky (Washington, DC: World Bank, 2021)
While trade exacerbates climate change, it is also a central part of the solution because it has the potential to enhance mitigation and adaptation. This timely report explores the different ways in which trade and climate change intersect. Trade contributes to the emissions that cause global warming and is itself also affected by climate change through changing comparative advantages. The report also confronts several myths concerning trade and climate change. The report focuses on the impacts of, and adjustments to, climate change in developing countries and on how future trade opportunities will be affected by both the changing climate and the policy responses to address it. The report discusses how trade can provide the goods and services that drive mitigation and adaptation. It also addresses how climate change creates immense challenges for developing countries, but also new opportunities to promote trade diversification in the transition to a low-carbon world. Suitable trade and environmental policies can offer effective economic incentives to attain both sustainable growth and poverty reduction.